2014
DOI: 10.4049/jimmunol.1302848
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic B Cell Depletion Disrupts CD4+ and CD8+ T Cell Homeostasis and Expansion during Acute Viral Infection in Mice

Abstract: B cells provide humoral protection against pathogens and promote cellular immunity through diverse nonclassical effector functions. To assess B cell function in promoting T cell homeostasis, mature B cells were either acutely or chronically depleted in mice using CD20 mAb. Acute B cell depletion in either 2- or 4-mo-old mice significantly reduced spleen and lymph node CD4+ and CD8+ T cell numbers, including naive, activated, and Foxp3+CD25+CD4+ regulatory T cell subsets. The numbers of IFN-γ– and TNF-α–produci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 71 publications
3
21
0
Order By: Relevance
“…Therefore, we quantified regulatory T cells (Tregs) in aorta and spleen using flow cytometry. As reported before 22 , absolute Treg number, but not the proportion of Treg (expressed as percentage of CD4+ T cells) was significantly lower in spleen following anti-CD20-mediated B cell depletion (Figure 6A). Staining of aortic cross-sections with CD3ε and FoxP3 antibodies demonstrated presence of Tregs in aortas of control antibody and anti-CD20 antibody treated mice (Figure 6B).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Therefore, we quantified regulatory T cells (Tregs) in aorta and spleen using flow cytometry. As reported before 22 , absolute Treg number, but not the proportion of Treg (expressed as percentage of CD4+ T cells) was significantly lower in spleen following anti-CD20-mediated B cell depletion (Figure 6A). Staining of aortic cross-sections with CD3ε and FoxP3 antibodies demonstrated presence of Tregs in aortas of control antibody and anti-CD20 antibody treated mice (Figure 6B).…”
Section: Resultssupporting
confidence: 82%
“…In the current study, we created B cell deficiency in mature WT mice by using anti-CD20 antibody which affected the homeostasis of T cells, primarily by reducing T cell number including Tregs in spleen as demonstrated by us and also reported previously by Lykken et al 22 Interestingly, IDO expressing pDC number was significantly increased in various tissues of B cell depleted mice. Moreover, B cell depletion has also been shown to improve endothelial function and reduce systemic inflammation in patients with rheumatoid arthritis 35 .…”
Section: Discussionsupporting
confidence: 66%
“…Of note in this regard, CD4 + T regulatory cells, like CD4 − CD8 − TCRαβ + T cells, also manifest a high rate of homeostatic proliferation (K. A. F. unpublished observations) and express many of the same effector and inhibitory proteins as CD4 − CD8 − TCRαβ + T cells [72]. Hence, our observations regarding the gene expression changes in homeostatically expanding CD8 + T cells may also apply to CD4 + T cells and, potentially to B cells, as it was recently observed that immunosuppressive IL-10-producing B cells preferentially repopulate the B cell pool following depletion with anti-CD20 Rituximab [73]. …”
Section: Discussionmentioning
confidence: 72%
“…23,24 Emerging paradigms reveal many non-antibody-dependent functions of B cells that could play important roles in atherosclerosis. [25][26][27] We and others have shown follicular B2 cell interactions with CD4 + T cells, antagonized by marginal zone B2 cells, promote pathogenic T cell responses in the atherosclerotic setting. [28][29][30][31][32][33] Few models have, therefore, addressed the specific role of antibodies in isolation without impacting on other B cell functions.…”
Section: Meet the First Author See P 198mentioning
confidence: 99%